1992
DOI: 10.1093/cvr/26.12.1206
|View full text |Cite
|
Sign up to set email alerts
|

Peptide leukotriene receptor antagonism in myocardial ischaemia and reperfusion

Abstract: LY-171883 has a protective effect in ischaemia-reperfusion injury to the myocardium. These findings suggest a role for peptide leukotrienes both in the extension of ischaemic damage and in post-ischaemic ventricular dysfunction during reperfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…Increased TXA 2 is associated with pulmonary fibrosis (12), whereas experiments using fibroblasts overexpressing 12-lipoxygenase have shown that these cells synthesize greater amounts of collagen I (13), the predominant type of collagen found in the heart and primarily responsible for cardiac fibrosis and increased myocardial stiffness (1). Furthermore, antagonism of LTD 4 /E 4 receptors during myocardial reperfusion reduced the size of the necrotic site and preserved cardiac function (46).…”
Section: Discussionmentioning
confidence: 99%
“…Increased TXA 2 is associated with pulmonary fibrosis (12), whereas experiments using fibroblasts overexpressing 12-lipoxygenase have shown that these cells synthesize greater amounts of collagen I (13), the predominant type of collagen found in the heart and primarily responsible for cardiac fibrosis and increased myocardial stiffness (1). Furthermore, antagonism of LTD 4 /E 4 receptors during myocardial reperfusion reduced the size of the necrotic site and preserved cardiac function (46).…”
Section: Discussionmentioning
confidence: 99%
“…LTD 4 /LTE 4 receptor antagonism reduced the extent of myocardial necrosis in a feline model of ischemia-reperfusion injury (68). Although, Hahn et al (69) found that CysLT receptor antagonism was not able to alter infarct size in coronary artery ligated dogs.…”
Section: Lo Metabolismmentioning
confidence: 97%
“…However, the role of CysLT 1 R in CVDs is rather controversial. Findings suggesting a role for cysteinyl LTs in the extension of ischemic damage and in cardiac dysfunction during reperfusion (Toki et al, 1988;Hock et al, 1992) are evenly balanced by results suggesting that these autacoids have no (Hahn et al, 1992) or little (Ito et al, 1989) contribution to the progression of myocardial ischemia-reperfusion injury. On the other hand, the LTRAs investigated in these studies belong to the first generation of molecules and may have not displayed enough potency to compete with the endogenous ligands, which are likely to be present with very high local bioavailability at sites where inflammatory cell accumulation and myocardial injury take place.…”
Section: New Potential Therapeutic Applications Of Leukotriene Recmentioning
confidence: 99%